Sensitivity and specificity of LDBio Aspergillus ICT lateral flow assay for diagnosing allergic bronchopulmonary aspergillosis in adult asthmatics - Sehgal, Inderpaul Singh; Muthu, Valliappan; Dhooria, Sahajal; Prasad, Kuruswamy Thurai; Rudramurthy, Shivaprakash M.; Aggarwal, Ashutosh Nath; Garg, Mandeep; Gangneux, Jean‐Pierre; Chakrabarti, Arunaloke; Agarwal, Ritesh (Mycoses, 2024)
Background Aspergillus fumigatus‐specific IgG estimation is crucial for diagnosing allergic bronchopulmonary aspergillosis (ABPA). A point‐of‐care LDBio immunochromatographic lateral flow assay (LFA) had 0%–90% sensitivity to detect IgG/IgM antibodies against A. fumigatus. Objective To assess the accuracy of LDBio‐LFA in diagnosing ABPA, using the modified ISHAM‐ABPA working group criteria as the reference standard. The secondary objective was to compare the diagnostic performance between LDBio‐LFA and A. fumigatus‐specific IgG (cut‐offs, 27 and 40 mgA/L), using a multidisciplinary team (blinded to A. fumigatus‐IgG and LDBio‐LFA results) diagnosis of ABPA as the reference standard. Methods We prospectively enrolled adult subjects with asthma and ABPA. We performed the LDBio‐LFA per the manufacturer's recommendations. We used the commercially available automated fluorescent enzyme immunoassay for measuring serum A. fumigatus‐specific IgG. We used the same serum sample to perform both index tests. The tests were performed by technicians blinded to the results of other tests and clinical diagnoses. Results We included 123 asthmatic and 166 ABPA subjects, with a mean ± SD age of 37.4 ± 14.4 years. Bronchiectasis and high‐attenuation mucus were seen in 93.6% (146/156) and 24.3% (38/156) of the ABPA subjects. The sensitivity and specificity of LDBio‐LFA in diagnosing ABPA were 84.9% and 82.9%, respectively. The sensitivity of serum A. fumigatus‐specific IgG ≥27 mgA/L was 13% better than LDBio‐LFA, with no difference in specificity. There was no significant difference in sensitivity and specificity between LDBio‐LFA and serum A. fumigatus‐IgG ≥40 mgA/L. Conclusion LDBio‐LFA is a valuable test for diagnosing ABPA. However, a negative test should be confirmed using an enzyme immunoassay.